The Performance Pipeline : Getting the Right Performance At Every Level of Leadership. - Drotter, Stephen (John Wiley & Sons, 2011)
The guide that defines the results required at each organizational level to sustain business success It's not enough to build a company full of people with leadership skills. The Performance Pipeline digs deep into the real work of executing business results at each leadership layer. Filled with lessons and examples from the author's 40 years of experienceShows how to set performance standards, make sure the right work is being done, and remove performance barriersIllustrates how leaders can make the transition to the next level and achieve full performance This book gives leaders in any indust.